The Extent Of Iraqi Laws In Response Of The International Agreements’ Requirements To Strive Against Drugs Crime (Al-Mansour Journal, 2022)
The history of human kind indicates that the humanity has known drugs or used them for a quite some time; in fact it has a history that is almost equal to the history of mankind.Although the problem of drugs is global, the international community did not pay attention to it but in the early twentieth century, whereas the complaints to fight this social disease have arisen after the situations of taking them have increased, and in spite of the high numbers of international agreements, covenants and protocols concerning this matter, drug taking and trading is still one of the biggest problems around the entire world in general and the Arabic countries in particular, as the latest statistics indicates that (15%) of the world’s population are taking these drugs.It is in our desire to shed the lights upon this dangerous disease and to reveal the best ways to strive against it, so we deemed appropriate to display our marked research (The extent of Iraqi laws in response of the international agreements’ requirements to strive against drugs crime) in three subjects, the first one is specialized in defining drugs and their types while the second one is dedicated to revealing the basis of drugs crime, however, the third one sheds the lights on the position of the international agreements and the Iraqi legislation in the fight against drugs crime.
Keywords: المواد المخدرة; اركان جریمة المخدرات; التشریع العراقي في مكافحة المخدرات